Análise da expressão gênica durante o reparo ósseo em defeitos de tíbias irradiados com laser terapêutico de baixa intensidade - Tim, Carla Roberta (2015)
This study aimed to evaluate the effects of low level laser therapy (LLLT) in the expression genes related to bone defect repair in tibia in rats. For this, one hundred male Wistar rats (3 months ± 250 g) were submitted to bilateral tibial defects and randomly distributed in two experimental groups (n=50). In the first study the effects of the LLLT in the expression of inflammatory and angiogenic genes in bone repair of rats were investigated in three groups: bone defect group (CG) and bone defect treated with laser 830nm (GL). Laser irradiation started immediately after the surgery and it was performed for two (36 h), three (3 days) or seven (7 days) sessions, with an interval of 24 hours between sessions. The application was punctual transcutaneously above the site of the injury. Rats were euthanized individually by carbon dioxide asphyxia in different set points (36 hours, 3 days and 7 days after surgery). Histopathological analysis showed that LLLT was able to modulate the inflammatory process in the area of the bone defect and to produce an earlier deposition of granulation tissue and newly formed bone. Microarray analysis demonstrated that LLLT produced an up-regulation of genes related to the inflammatory processes (MMD, PTGIR, PTGS2, Ptger2, IL1, 1IL6, IL8, IL18) and angiogenic genes (FGF14, FGF2, ANGPT2, ANGPT4 and PDGFD) at 36 h and 3 days, followed by a decrease of the gene expression on day 7. Immunohistochemical analysis revealed that treated animals presented a higher expression of COX-2 at 36 h after the surgery and an increased VEGF expression on days 3 and 7. Our findings indicate that LLLT was efficient on accelerating the development of newly formed bone probably by modulating the inflammatory and angiogenic gene expression and COX2 and VEGF immunoexpression during the initial phase of bone healing. In the second study, aspects related to bone cell stimulation and newly formed bone were evaluated in five groups: CG and LG. The laser treatment started immediately after the surgery to produce the bone defects and there have been 1, 2, 3, 5 e 7 sessions with an interval of 24 hours. Rats were euthanized in different set points (12 hours, 36 hours, 3 days, 5 days and 7 days after surgery). Histopathology revealed that treated animals produced increased amount of newly formed bone at the site of the injury. Also, microarray analysis evidenced that LLLT produced a significantly increase in the expression TGF-β, BMP, FGF, RUNX-2 and BMP, which could have stimulated osteoblast proliferation and differentiation, which may be related to improving the deposition of newly formed bone at the site of the injury. Thus, it is possible to concluded that LLLT improved bone healing by producing a significant increase in the expression of osteogenic genes. Finally, we concluded that LLLT was effective to stimulate newly formed bone by active expression of inflammatory, angiogenic and osteogenic genes and also stimulate immunoexpression of proteins related to the initial phases of bone healing in tibial defects in rats.